Detection and isolation of relapsing fever spirochete, Borrelia miyamotoi, from Ixodes ricinus collected in the Czech Republic: separation of relapsing fever and Lyme disease spirochetes by cultivation on solid medium - Kienberger, Angela (Jihočeská univerzita, 2023)
In this bachelor thesis, the focus of the study was on a newly discovered tick-born pathogen named Borrelia miyamotoi, which belongs to the relapsing fever group and is transferred by the same Ixodes species that transmit Lyme disease spirochetes. Very little is still known about the cultivation of B. miyamotoi in-vitro, whereas it is of great importance since detailed characterization of the pathogen is necessary. Therefore, the interest of developing successful solid or liquid media for B. miyamotoi in-vitro cultivation is steadily increasing. The aim of this thesis was to detect the presence of pathogenic for humans Borrelia miyamotoi in hard ticks collected from different areas of the Czech Republic and to obtain a monoclonal population of B. miyamotoi, while separating co-infected cultures on plates with solid medium.
Detection and isolation of relapsing fever spirochete, Borrelia miyamotoi, from Ixodes ricinus collected in the Czech Republic: separation of relapsing fever and Lyme disease spirochetes by cultivation on solid medium
Keywords: \kur{Borrelia miyamotoi}; \kur{Borrelia burgdorferi} sensu lato; \kur{Ixodes ricinus}; Co-infections; Nested PCR; Reverse line blotting; monoclonal culture; mice-infection; MKP-F medium; plating; modified plating medium; molecular cloning; \kur{Borrelia miyamotoi}; \kur{Borrelia burgdorferi} sensu lato; \kur{Ixodes ricinus}; Co-infections; Nested PCR; Reverse line blotting; monoclonal culture; mice-infection; MKP-F medium; plating; modified plating medium; molecular cloning